(untitled) - Moaveni, Saeed (Australia, 2018)
The book helps students to understand the connections among earth’s finite resources and the environmental, social, ethical, technical, and economical factors impacted by daily decisions. This book teaches students how to evaluate these important issues and make environmentally sound decisions.
Keywords: Năng lượng tái sinh,Tòa nhà bền vững,Renewable energy sources,Sustainable buildings